Exposure to Noise or Music in Clinical Trials: A Scoping Review on Ethical and Methodological Considerations - Eleftheria Iliadou; Vasileios Bitzios; Konstantinos Pastiadis; Christopher J. Plack; Athanasios Bibas (Noise and Health, 2024)
Background: Use of noise or music in experimental human studies requires balancing the need to avoid subjecting participants to potentially harmful noise levels while still reaching levels that will produce a measurable change in the primary outcome. Several methodological and ethical aspects must be considered. This study aims to summarize ethical and methodological aspects, and reported outcomes, of previously published experimental paradigms using loud noise/music. Methods and materials: Four databases (Medline, Central, Web of Science, and Scopus) and two trials registries (Clinicaltrials.gov and EU Clinical Trials) were searched. Extracted items had the details of author and year of publication, study design and purpose, population, setting timeline and material, selected battery test, and effect of noise/music on participants’ hearing. Results: Thirty-four studies were included. Exposure safety considerations were reported in five studies. Eleven studies assessing hearing loss used white or narrow-band noise [(NBN (0.5–4 kHz), up to 115 dBA, duration range: 3′–24 hours)], and 10 used pop music (up to 106 dBA, duration range: 10′–4 hours). Experimental setting varied significantly. Temporary thresholds shift (TTS) and reduction in distortion product otoacoustic emissions were found at 1–8 kHz, with maximum average TTS∼21.5 dB at 4 kHz after NBN and ∼11.5 dB at 6 kHz after music exposure. All participants recovered their hearing, except for one participant in one study. In the 13 non-hearing loss studies, no hearing testing was performed after exposure, but loud noise was associated with temporary stress, bradygastria, and cardiovascular changes. Noise-induced subjective stress may be higher for participants with tinnitus. Loud noise (100 dBA, 10′) increased diastolic and mean blood pressure only in participants with hypertension. Conclusion: Experimental exposure paradigms can produce temporary changes to hearing without measurable long-term health consequences. Methodological and ethical aspects identified in this review should be considered for the development of future paradigms.